Spellslinger eaudiobook - de Castell, Sebastien (Spellslinger, 2018)
A would-be mage with no magic of his own has to defeat powerful enemies with only cunning and deception in the first book of an exciting adventure fantasy series from Sebastien de Castell. Kellen is moments away from facing his first duel and proving his worth as a spellcaster. There's just one problem: his magic is fading. Facing exile unless he can pass the mage trials, Kellen is willing to risk everything — even his own life — in search of a way to restore his magic. But when the enigmatic Ferius Parfax arrives in town, she challenges him to take a different path. One of the elusive Argosi, Ferius is a traveller who lives by her wits and the cards she carries. Daring, unpredictable, and wielding magic Kellen has never seen before, she may be his only hope. The first novel in a compelling six-book series, bursting with tricks, humor, and a whole new way to look at magic. Spellslinger Series Spellslinger Shadowblack Charmcaster For more from Sebastien de Castell, check out: The Greatcoats Quartet Traitor's Blade Saint's Blood Knight's Shadow Tyrant's Throne